Implementasi Aplikasi Pengadilan Elektronik (E-Court) untuk Meningkatkan Pelayanan Publik di Pengadilan Negeri Pulang Pisau - Lia Amelia; Muhammad Aidil; Vega Selvia; Salmah Salmah; Sri Hidayati; Ramadhani Alfin Habibie; Kamal Hasuna (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
With the emergence of a vast internet network, the 4.0 industrial revolution is transforming human lifestyles from conventional to modern and impacting various aspects of life, such as culture, social, and economy. The Pulang Pisau District Court uses the e-Court application, which consists of four main features: online case registration (e-filing), fee payment (e-Payment), electronic summons (e-summons), and online conference (e-ligation), launched by the Supreme Court on October 13, 2018. Data collected from various sources in this research were gathered through a qualitative literature study approach. The focus of the research is on how the e-Court application can enhance the efficiency and ease of accessing legal services for the community. The research results show that the electronic court system not only speeds up the legal administration process but also enhances the transparency and accountability of the judicial system. By launching this application, the Supreme Court is making a significant change in the reform of Indonesia's judiciary, making the judicial system cheaper, faster, and simpler for all citizens. It is hoped that the e-Court application can meet the global community's needs to face legal challenges in the digital era.